Representation of tawhid values in the WhatsApp channel “daily Islamic” - Mohammad Ali Danial; Aulia Nurrohmah; Qurrotul Aini (Institute for Advanced Science, Social, and Sustainable Future, 2026)
Background: The development of social media has changed the landscape of Islamic preaching from physical spaces to more interactive and dynamic digital spaces. This phenomenon presents opportunities for strengthening Islamic spirituality, particularly the values of tawhid, through media that are close to the lives of the younger generation. However, studies on the representation of tawhid values in digital preaching, especially on instant messaging platforms such as WhatsApp, are still rare. This study aims to analyze how the Daily Islamic channel represents tauhid messages in its da'wah content, as well as how the style of delivery and audience reactions contribute to strengthening spiritual meaning in the context of modern life. Methods: This study uses a qualitative approach with content analysis and online observation methods. Data was obtained purposively from Daily Islamic posts during the period of September to October 2025, which contained text messages, reflective quotes, and Islamic visuals relevant to the value of tawhid. All data were documented in the form of screenshots and analyzed inductively through the three main dimensions of tauhid, namely rubūbiyyah, ulūhiyyah, and asmā’ wa ṣifāt. The analysis was carried out by examining the message structure, diction, style of language, and audience responses to interpret the theological and spiritual meanings that emerged. Findings: The Daily Islamic channel presents a representation of tawhid that is not only theoretical but also practical through messages about gratitude, patience, trust in God, and prayer. These messages are communicated in a warm, reflective, and empathetic style that awakens the spiritual awareness of the audience to connect every event in life with God's plan. The positive reaction of the audience shows that an empathetic communicative approach is able to bridge theological values with the emotional needs of the digital generation. Conclusion: Digital da'wah through the Daily Islamic channel serves as a medium for shaping contextual and inspirational awareness of tawhid, presenting Islamic spirituality that is close to the psychological reality of modern society. Novelty/Originality of this article: This study offers a new perspective on digital da'wah based on the values of tawhid by focusing its analysis on religious messages on the WhatsApp platform, a communication space that is rarely studied but has great potential in shaping the spirituality of the younger generation.